List dedykacyjny Mikołaja Radziwiłła jako program ideowy Biblii Brzeskiej. Wokół humanistycznych kontekstów i uwarunkowań studiów biblijnych - Nastulczyk, Tomasz (Tematy i Konteksty, 2014)
This paper deals with the ideological programme of the Brest Bible, expressed in the letter of dedication by Mikołaj Radziwiłł, addressed to the Polish King Sigismund II Augustus. The first part is a short introduction to the problem of biblical humanism of the 16th century. The second and third part deal directly with the letter of dedication. The author focuses on the two ancient rulers mentioned in the letter: Ptolemy II Philadelphus (protector of Septuagint) and the Old Testament Josiah (renewer of the Law). A detailed analysis reveals that the categories of biblical humanism, which shaped the description of both kings, were used to create the parenetic role models, which were to persuade the king to personally take care of the Brest Bible. The last part of the paper points to the problem of gradual confessionalization of biblical humanism. The indirect, allusive introduction of the third royal role model (the Old Testament Manasseh, repenting idolator and destroyer of the Temple idol) suggests that according to the letter of dedication, the final consequence of embracing biblical humanism is to become a devoted supporter of the Reformation.